Domestication Origin and Breeding History of the Tea Plant (Camellia sinensis) in China and India Based on Nuclear Microsatellites and cpDNA Sequence Data - Meegahakumbura, Muditha K.; Wambulwa, Moses C.; Li, Miao-Miao; Thapa, Kishore K.; Sun, Yong-Shuai; Möller, Michael; Xu, Jian-Chu; Yang, Jun-Bo; Liu, Jie; Liu, Ben-Ying; Li, De-Zhu; Gao, Lian-Ming (Frontiers in Plant Science, 2018)
Although China and India are the two largest tea-producing countries, the domestication origin and breeding history of the tea plant in these two countries remain unclear. Our previous study suggested that the tea plant includes three distinct lineages (China type tea, Chinese Assam type tea and Indian Assam type tea), which were independently domesticated in China and India, respectively. To determine the origin and historical timeline of tea domestication in these two countries we used a combination of 23 nSSRs (402 samples) and three cpDNA regions (101 samples) to genotype domesticated tea plants and its wild relative. Based on a combination of demographic modeling, NewHybrids and Neighbour joining tree analyses, three independent domestication centers were found. In addition, two origins of Chinese Assam type tea were detected: Southern and Western Yunnan of China. Results from demographic modeling suggested that China type tea and Assam type tea first diverged 22,000 year ago during the last glacial maximum and subsequently split into the Chinese Assam type tea and Indian Assam type tea lineages 2770 year ago, corresponding well with the early record of tea usage in Yunnan, China. Furthermore, we found that the three tea types underwent different breeding histories where hybridization appears to have been the most important approach for tea cultivar breeding and improvements: a high proportion of the hybrid lineages were found to be F2 and BCs. Collectively, our results underscore the necessity for the conservation of Chinese Assam type tea germplasm and landraces as a valuable resource for future tea breeding.